ADIPONECTIN SERUM LEVEL DIFFERENCE IN WOMEN WITH ENDOMETRIOTIC AND NON-ENDOMETRIOTIC CYSTS - Ruswana Anwar; Fahdiansyah Fahdiansyah (Journal of Medicine and Health, 2015)
Endometriosis is an estrogen-dependent disease. Low levels of adiponectin resulted in an increased free estrogen levels and the inability to inhibit angiogenesis and the inflammatory process resulting in the development of increasingly severe endometriosis.This study is aimed to determine the differences in serum adiponectin levels in patient with nonendometriotic cyst with endometriosis cyst and its relationship with endometriosis stages. This is an analytical comparative study with cross-sectional method in group of women with endometriotic cyst (n=25) and women with non-endometriotic cysts (n=25), performed either laparoscopic or laparotomy surgery. The serum levels of adiponectin in both groups then compared with statistical analysis.The results showed there were no significant differences (p>0,05) on the characteristics of the study subjects in terms of age (p=0.994) and BMI (p=0.27). Significant differences of adiponectin levels were found between endometriotic patient group (mean=3.91) and nonendometriotic patients group (mean=8.59). There were no significant differences of adiponectin level in stages III endometriosis (mean = 4.24) and stage IV endometriosis (mean = 3.54).It is concluded that serum adiponectin levels in patients with endometriosis is lower than patient with non-endometriotic cyst. There is no relationship between adiponectin levels with endometriosis stage.Â Keywords: adiponectin, endometriotic cyst, non-endometriotic cyst, endometriosis stage